Implementasi Pendekatan Sistemik dalam Pembelajaran PAI - Ama Faridatul Husna Jamil (Al-Munawwarah : Jurnal Pendidikan Islam, 2022)
This study explains the importance of components management in Islamic Education Learning (PAI) by using the effective approach attempting to depict the concept and implementation of a systematic approach in learning Islamic Education (PAI) that can be one of the references for Islamic Education teachers. Islamic Education is known as one of the learnings having a highly complicated problem. Many Islamic Education Learnings materials are in doctrine forms requiring the involvement of superior belief. In addition, the aim of Islamic Education Learning is difficult to achieve. Hence, this issue needs an effective approach and management. Implementing an effective approach capable of strengthening Islamic Education Learning is one of the solutions. The educators can use a systematic approach that aims to help the students in understanding the relationship between the concept and materials, such as the discussion between materials in one field of study. Therefore, the result of systematic learning will form and develop the students’ understanding as well as their comprehensive framework of thinking so that they have a thorough understanding as implementation supplies of Islamic Education Learning in their actual life.